Nitrate Reductase Knockout Uncouples Nitrate Transport from Nitrate Assimilation and Drives Repartitioning of Carbon Flux in a Model Pennate Diatom. Issue 8 (1st August 2017) - McCarthy, James K.; Smith, Sarah R.; McCrow, John P.; Tan, Maxine; Zheng, Hong; Beeri, Karen; Roth, Robyn; Lichtle, Christian; Goodenough, Ursula; Bowler, Chris P.; Dupont, Christopher L.; Allen, Andrew E.
Abstract : Genetic inactivation of diatom nitrate reductase abolishes nitrate assimilation but not nitrate uptake and results in transcriptional activation of nitrate storage and triacylglycerol biosynthesis pathways. Abstract: The ecological prominence of diatoms in the ocean environment largely results from their superior competitive ability for dissolved nitrate (NO3   − ). To investigate the cellular and genetic basis of diatom NO3   − assimilation, we generated a knockout in the nitrate reductase gene ( NR -KO) of the model pennate diatom Phaeodactylum tricornutum . In NR -KO cells, N-assimilation was abolished although NO3   − transport remained intact. Unassimilated NO3   − accumulated in NR -KO cells, resulting in swelling and associated changes in biochemical composition and physiology. Elevated expression of genes encoding putative vacuolar NO3   − chloride channel transporters plus electron micrographs indicating enlarged vacuoles suggested vacuolar storage of NO3   − . Triacylglycerol concentrations in the NR -KO cells increased immediately following the addition of NO3   −, and these increases coincided with elevated gene expression of key triacylglycerol biosynthesis components. Simultaneously, induction of transcripts encoding proteins involved in thylakoid membrane lipid recycling suggested more abrupt repartitioning of carbon resources in NR -KO cells compared with the wild type. Conversely, ribosomal structure and photosystem genes were immediately deactivated in NR -KO cells following NO3   − addition, followed within hours by deactivation of genes encoding enzymes for chlorophyll biosynthesis and carbon fixation and metabolism. N-assimilation pathway genes respond uniquely, apparently induced simultaneously by both NO3   − replete and deplete conditions.